Effects of accountable care and payment reform on substance use disorder treatment: evidence from the initial 3 years of the alternative quality contract. (24th September 2016) - Stuart, Elizabeth A.; Barry, Colleen L.; Donohue, Julie M.; Greenfield, Shelly F.; Duckworth, Kenneth; Song, Zirui; Mechanic, Robert; Kouri, Elena M.; Ebnesajjad, Cyrus; Chernew, Michael E.; Huskamp, Haiden A.
Abstract: Background and Aims: Global payment and accountable care reform efforts in the United States may connect more individuals with substance use disorders (SUD) to treatment. We tested whether such changes instituted under an Alternative Quality Contract (AQC) model within the Blue Cross Blue Shield of Massachusetts' (BCBSMA) insurer increased care for individuals with SUD. Design: Difference‐in‐differences design comparing enrollees in AQC organizations with a comparison group of enrollees in organizations not participating in the AQC. Setting: Massachusetts, USA. Participants: BCBSMA enrollees aged 13–64 years from 2006 to 2011 (3 years prior to and after implementation) representing 1 333 534 enrollees and 42 801 SUD service users. Measurements: Outcomes were SUD service use and spending and SUD performance metrics. Primary exposures were enrollment into an AQC provider organization and whether the AQC organization did or did not face risk for behavioral health costs. Findings: Enrollees in AQC organizations facing behavioral health risk experienced no change in the probability of using SUD services (1.64 versus 1.66%; P  = 0.63), SUD spending ($2807 versus $2700; P  = 0.34) or total spending ($12 631 versus $12 849; P  = 0.53), or SUD performance metrics (identification: 1.73 versus 1.76%, P  = 0.57; initiation: 27.86 versus 27.02%, P  = 0.50; engagement: 11.19 versus 10.97%, P  = 0.79). Enrollees in AQC organizations not at risk for behavioral health spending experienced a small increase in the probability of using SUD services (1.83 versus 1.66%; P  = 0.003) and the identification performance metric (1.92 versus 1.76%; P  = 0.007) and a reduction in SUD medication use (11.84 versus 14.03%; P  = 0.03) and the initiation performance metric (23.76 versus 27.02%; P  = 0.005). Conclusions: A global payment and accountable care model introduced in Massachusetts, USA (in which a health insurer provided care providers with fixed prepayments to cover most or all of their patients' care during a specified time‐period, incentivizing providers to keep their patients healthy and reduce costs) did not lead to sizable changes in substance use disorder service use during the first 3 years following its implementation.